MEAN WIND AND POTENTIAL TEMPERATURE PROFILES IN THE ATMOSPHERIC SURFACE LAYER: FURTHER INVESTIGATIONS - Edi Santoso (Jurnal Sains & Teknologi Modifikasi Cuaca, 2000)
The surface layer theory will be presented. Monin – Obukhov similarity theory has played a leading role in most attempts to interpret experimental data on surface layer turbulence. It will also be showed how investigators have modified it for convective conditions. It presents methods for coupling surface layer profiles to profiles higher in the atmospheric boundary layer as well. Most investigators preferred to remain within the classical paradigm that strongly dependent on surface parameters. However, the results based on the classical approach did not merge smoothly into the uniform layer. The new results that considered parameters above surface layer gave better matching to the whole profile.Di dalam tulisan ini akan disajikan perkembangan teori lapisan permukaan. Teorikemiripan Monin – Obukhov memegang peranan penting di dalam setiap usaha untukmenganalisis data turbulen lapisan permukaan dari lapangan. Juga akan dibahasbagaimana para peneliti memodifikasi teori tersebut untuk kondisi atmosfir yang konvektif. Berbagai metoda dikembangkan untuk menggabungkan profil dekatpermukaan dengan profil di bagian atasnya. Sebagian besar para peneliti tetapberpegang pada teori klasik yang mempertimbangkan secara kuat parameter-parameterpermukaan. Pendekatan lebih baru yang mempertimbangkan parameter-parameter yang ada di lapisan lebih atas memberikan hasil yang lebih baik.